Characterization of Au Thin Film at Different Thicknesses - Binti Selamat, Nur Syafiqah; Ahmad Hadi Ali, (Enhanced Knowledge in Sciences and Technology, 2024)
In addressing the challenge of achieving efficient electrical contacts on light-emitting diodes (LEDs) characterized by inherent low contact resistance, this work delves into the comprehensive characterization of gold (Au) thin films deposited on n-type silicon (Si) and glass substrates using the DC magnetron sputtering technique. A systematic variation of film thickness ranging from 10 to 50 minutes is executed, and an array of advanced techniques, including ellipsometry, Atomic Force Microscopy (AFM), Scanning Electron Microscopy (SEM), a four-point probe, and Ultraviolet-visible spectroscopy (UV-Vis), is employed for thorough analysis. The research discerns nuanced correlations among film thickness, surface topology, structural morphology, electrical properties, and optical characteristics. These findings, situated at the intersection of nanotechnology and thin film engineering, contribute to an enhanced understanding of the intricate interplay among these vital factors, offering valuable insights for future technological advancements.